2006
DOI: 10.1021/ic0506815
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of Metal−Sulfur Vibrations in an Oxo-Molybdenum Dithiolene Complex:  Relevance to Sulfite Oxidase

Abstract: X-ray crystallography and resonance Raman (rR) spectroscopy have been used to further characterize (Tp*)MoO(qdt) (Tp* is hydrotris(3,5-dimethyl-1-pyrazolyl)borate and qdt is 2,3-quinoxalinedithiolene), which represents an important benchmark oxomolybdenum mono-dithiolene model system relevant to various pyranopterin Mo enzyme active sites, including sulfite oxidase. The compound (Tp*)MoO(qdt) crystallizes in the triclinic space group, P1, where a = 9.8424 (7) A, b = 11.2323 (8) A, c = 11.9408 (8) A, alpha = 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 81 publications
3
54
0
Order By: Relevance
“…We have previously used this orthogonal enhancement spectroscopic signature to assign electronic transitions to the Mo(dx 2 −y 2 ) and Mo(dxz,yz) acceptor orbitals in oxomolybdenum complexes. 34,35 In MoO(SPh) 2 ( i Pr 2 Dt o ), resonance enhancement of the Mo-dithione S-Mo-S stretching mode is anticipated for transitions from filled thiol and Mo(dx 2 −y 2 ) based MOs to the dithione based LUMO, which also possesses in-plane Mo(dx 2 −y 2 ) character. Resonance enhancement of the Mo≡O stretch is anticipated for transitions to the higher energy Mo(dxz,yz) virtual orbital set since the Mo(dxz,yz) orbitals possess Mo≡O π* character and electron occupation of Mo≡O π* orbitals will result in large excited state distortions along the Mo≡O bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously used this orthogonal enhancement spectroscopic signature to assign electronic transitions to the Mo(dx 2 −y 2 ) and Mo(dxz,yz) acceptor orbitals in oxomolybdenum complexes. 34,35 In MoO(SPh) 2 ( i Pr 2 Dt o ), resonance enhancement of the Mo-dithione S-Mo-S stretching mode is anticipated for transitions from filled thiol and Mo(dx 2 −y 2 ) based MOs to the dithione based LUMO, which also possesses in-plane Mo(dx 2 −y 2 ) character. Resonance enhancement of the Mo≡O stretch is anticipated for transitions to the higher energy Mo(dxz,yz) virtual orbital set since the Mo(dxz,yz) orbitals possess Mo≡O π* character and electron occupation of Mo≡O π* orbitals will result in large excited state distortions along the Mo≡O bond.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 For these higher valent oxomolybdenum dithiolenes, dithiolene → Mo(dx 2 −y 2 ) LMCT character admixed into the ground state is responsible for dithiolene ligand folding (Figure 2). 35,3841 …”
Section: Resultsmentioning
confidence: 99%
“…17 Similar folding distortions have also been observed in bis(cyclopentadienyl)-ML n complexes with a single dithiolene ligand and other Mo mono-dithiolene complexes. 18,19 In addition to the different geometric structures of complexes with dithiolene ligands, it has also been found that dithiolene complexes have interesting redox properties, specifically the question of ligand-vs. metal-based oxidation (ie. non-innocent vs. innocent).…”
Section: Introductionmentioning
confidence: 99%
“…Additional support for this assignment is based on polarized rR spectra of the benchmark Mo-ditholene complex Tp*Mo(bdt) (bdt = benzene-1,2-dithiolate), where the S–Mo–S symmetric stretch and bend are observed at 393 and 362 cm –1 , respectively. 21,22 Although low-frequency rR data for pyranopterin molybdenum enzymes are sparse, vibrational data for dimethyl sulfoxide reductase (DMSOR) have been collected and analyzed. 2327 In contrast to XO/XDH, DMSOR family enzymes possess two pyranopterin ditholenes bound to the Mo ion.…”
mentioning
confidence: 99%